Diagnosis of complications in auxiliary heterotopic partial-liver transplant recipients: Spiral CT findings - N. Çagla TARHAN; Ali FIRAT; Mehmet COŞKUN; Mehmet HABERAL (Turkish Journal of Gastroenterology, 2019)
-